PRODUKTIVITAS SERASAH MANGROVE DI DESA POPALO GORONTALO UTARA - Puspaningrum, Dian; Ruruh, Alexander; Imran, Aprialdi Agus (MAKILA, 2024)
Popalo Village is located in Anggrek Sub-district, one of the sub-districts administratively located in Gorontalo Utara Regency, and has a mangrove area of 51.08 hectares. Some conditions of mangrove areas in Popalo Village have changed land use into ponds by the community; this has led to concerns about a decrease in the function and role of mangrove areas as nutrient converters. This study was conducted to determine the productivity and decomposition rate of litter of each component, including leaves, twigs, fruits, and flowers in mangrove vegetation, and the percentage of mangrove litter decomposition. The research method was sampling using litter traps with observation time every 15, 30, 45, and 60 days. The analysis carried out was to calculate the productivity of mangrove leaf, twig, fruit, and flower litter—the decomposition rate and percentage of litter decomposition of each mangrove component. The results showed that litter productivity in each part of the mangrove plant, namely leaves, twigs, flowers, and fruit that became the research sample, experienced a downward trend during the 60 days of observation, while the results of the percentage of decomposition showed a fluctuating trend. This condition is caused by several environmental factors essential to decomposing litter. Influencing factors include temperature at the research site, seawater salinity, daily tides, and the activity of microorganisms in the soil that support the decomposition process.